Upaya Indonesia Menjaga dan Meredam Konflik Diwilayah Laut NKRI Terutama Diwilayah Perbatasan Laut Cina Selatan Dikawasan Natuna Kepulauan Riau - Rahmadhan Tri Syahputra; Syafira Caesar Rani; Zada Idderigsa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
In writing this journal, I as the writer want to describe and present topics regarding issues that are often hot and often become conflicts in our country, the Republic of Indonesia, regarding the border area at the tip of the northern region of Indonesia or what is widely known to the general public is called